High-gradient fields in magnets with giant anisotropy - Samofalov, V.N.; Belozorov, D.P.; Ravlik, A.G. (Functional Materials, 2008)
The gradient of strong stray fields generated by various systems of permanent magnets with giant magnetic anisotropy has been calculated. It is shown that the gradient values near singular points are characterized by the dependence ∇H ≈ AMs(1/r), where A is a constant for this system of magnets, Ms is the saturation magnetization of the magnet material, r is the distance from the singular point. The field gradient in those areas may reach about 10⁶ to 10⁸ Oe/cm. The indicated gradient level is comparable with maximum values achieved in superconducting solenoids supplied with the conical tips produced of soft magnetic material with high Ms. It is established that the volume forces with the specific density of f ≈ 4Ms²/r arise near singular points in the magnet material being in high-gradient field. The mechanical stress in a magnet caused by these forces is characterized by the dependence σ ≈ 4πMs²ln(a/Xmin) and may reach 2-3 kg/mm². Обчислено градієнт сильних полів розсіяння, що генеруються різними системами з постійних магнітів з гігантською магнітною анізотропією. Показано, що величина градієнта поблизу сингулярних точок характеризується залежністю ∇H ≈ AMs(1/r), де А - певна стала для даної системи магнітів. Градієнт поля може сягати значень порядку 10⁶-10⁸ Е/см. Вказаний рівень градієнта є порівнянним з граничними його величинами, які досягаються у надпровідних магнітах з конічними наконечниками, виготовленими з магнітом'яких матеріалів з високою індукцією. Встановлено, що у високоградієнтному полі у матеріалі магніту поблизу сингулярних точок виникають об'ємні сили з питомою густиною f ≈ 4Ms²/r. Механічні напруги у магніті, пов'язані з цими силами, характеризуються залежністю σ ≈ 4πMs²ln(a/Xmin) і можуть досягати значень 2-3 кг/мм². Рассчитан градиент сильных полей рассеяния, генерируемых различными системами из постоянных магнитов с гигантской магнитной анизотропией. Показано, что величина градиента вблизи сингулярных точек характеризуется зависимостью ∇H ≈ AMs(1/r), где А - некоторая постоянная для данной системы магнитов. Вблизи сингулярных точек I∇HI может достигать значений I∇HI ≈ 10⁶-10⁸ Э/см. Указанные значения градиента поля сравнимы с предельными его величинами, которые достигаются в сверхпроводящих магнитах с коническими наконечниками, изготовленными из материалов с высокой индукцией. Установлено, что в высокоградиентном поле в материале магнита вблизи сингулярных точек возникают объёмные силы с удельной плотностью f ≈ 4Ms²/r. Механические напряжения в магните, связанные с этими силами, характеризуются зависимостью σ ≈ 4πMs²ln(a/Xmin) и могут достигать значений 2-3 кг/мм².